Suspicious Financial Transactions from Initial Evidence of Customs Offenses - Yuni Priskila Ginting; Sabela, Louise Shania (LPPM Universitas Ekasakti Padang, 2024)
This study focuses on the critical issue of suspicious financial transactions related to customs offenses in Indonesia. The research aims to analyze the evidence system for customs offenses, the utilization of suspicious financial transactions as initial evidence, and strategies to enhance the evidence system. Using a normative legal methodology, the study examines Indonesia's legislative frameworks and empirical case studies to interpret legal principles and regulations governing customs-related financial transactions. Results indicate that increased trade volume correlates with a rise in customs-related financial irregularities, leading to significant financial losses for the state. Effective monitoring and enforcement by customs authorities are crucial in combating these offenses. Recommendations include refining the regulatory framework for identifying suspicious transactions, enhancing the capabilities of customs and law enforcement agencies through training and technology, and strengthening international cooperation to effectively address cross-border financial crimes.